ANALISIS TINGKAT LIKUIDITAS PT. ADIRA DINAMIKA MULTI FINANCE TBK. CABANG SAMARINDA PADA TAHUN 2014-2018 - Umi Kulsum3, Annisa Widyasari 1, Imam Nazarudin Latif (EKONOMIA, 2021)
This study aims: to determine and analyze the liquidity level of the average value of PT. Adira Dinamika Multi Finance Tbk. Samarinda Branch is reviewed from the current ratio for 2014-2018, to analyze the liquidity level of the average value in terms of the 2014-2018 quick ratio. to analyze the liquidity level of the average value in terms of the cash ratio (cash ratio) in 2014-2018.               The data used in this study were obtained from PT. Adira Dinamika Multi Finance Tbk. Samarinda Branch 2014-2018 period and other sources related to this research. Liquidity analysis uses Current Ratio, Quick Ratio, and Cash ratio analysis in each period 2014-2018.               Based on the results of research and discussion of Liquidity Analysis, the Current Ratio in 2014-2015 has increased, in 2015-2016 it has increased, in 2016-2017 it has decreased, in 2017-2018 the ratio has not changed. The Quick Ratio level in 2014-2015 has increased, in 2015-2016 it has increased, in 2016-2017 it has decreased, and in 2017-2018 it has not changed. The level of Cash Ratio in 2014-2015 decreased, in 2015-2016 there was no change, in 2016-2017 it increased, and in 2017-2018 it decreased.               The level of liquidity in terms of the Current Ratio Current Ratio, fluctuations in the 2014-2018 period did not reach the predetermined ratio value, so the hypothesis was rejected. The level of liquidity in terms of the Quick Ratio, fluctuations occurred in the 2014-2018 period and did not reach the predetermined ratio value, so the hypothesis was rejected. The level of liquidity in terms of cash ratios. Cash Ratio fluctuations occurred in the 2014-2018 period and did not reach the predetermined ratio value, the hypothesis was rejected